2019
DOI: 10.1038/s41467-019-13542-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mutant p53 drives clonal hematopoiesis through modulating epigenetic pathway

Abstract: Clonal hematopoiesis of indeterminate potential (CHIP) increases with age and is associated with increased risks of hematological malignancies. While TP53 mutations have been identified in CHIP, the molecular mechanisms by which mutant p53 promotes hematopoietic stem and progenitor cell (HSPC) expansion are largely unknown. Here we discover that mutant p53 confers a competitive advantage to HSPCs following transplantation and promotes HSPC expansion after radiation-induced stress. Mechanistically, mutant p53 i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 63 publications
1
54
0
3
Order By: Relevance
“…Some of these p53 mutations have been shown to be a result of clonal hematopoiesis. This is a process whereby expansion of blood cell clones occurs due to advantageous somatic mutations, which often accumulate with age, and may contribute to hematological malignancies [35][36][37][38]. Having a broad NGS panel, that can simultaneously detect multiple low frequency variants becomes critical in defining the significance of circulating mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these p53 mutations have been shown to be a result of clonal hematopoiesis. This is a process whereby expansion of blood cell clones occurs due to advantageous somatic mutations, which often accumulate with age, and may contribute to hematological malignancies [35][36][37][38]. Having a broad NGS panel, that can simultaneously detect multiple low frequency variants becomes critical in defining the significance of circulating mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, three mutp53 versions (R248W, R273H and R175H) showed increased association with EZH2 (Enhancer of Zeste Homolog 2), which is part of PCR2 (Polycomb Repressive Complex-2), compared with wtp53, improving EZH2 binding to chromatin. Nonetheless, mutp53 promoted the presence of H3K27me3 rather than altering genomic distribution (Chen et al, 2019 ). Moreover, mutp53 also indirectly upregulates EZH2 by attenuating miR-26a, a negative regulator of EZH2, supporting another mechanism in the regulation of EZH2 activity (Jiang et al, 2015 ).…”
Section: Impact Of Mutp53 Gain-of-functionmentioning
confidence: 99%
“…These mutant p53/transcription factor interactions lead to changes in expression of both protein coding genes and a range of different noncoding RNAs, including miRNAs and lncRNAs (Zhang et al 2020a), all of which can contribute to the GOF phenotype. The activity of mutant p53s is further expanded by the ability to bind and modulate the activity of nontranscription factor proteins, resulting in the impairment of the DNA damage response, increased rates of glycolysis and lipid production (Zhu et al 2020), and increased histone methylation (Chen et al 2019). More generally, mutant p53s can bind to a variety of proteins controlling the epigenome, including those that regulate chromatin structure, histone modifications, and splicing, resulting in genome-wide dysregulation (Escobar-Hoyos et al 2020;Zhang et al 2020a).…”
Section: Oncogenic Gains Of Functionmentioning
confidence: 99%